Correlates of Moderate-to-Vigorous Physical Activity and Exercise Motivation in Underserved African American Men - Abshire, Demetrius A. (Am J Mens Health, 2019)
Effective interventions are needed to increase physical activity (PA) in African American men, but little is known about correlates of PA and exercise motivation in this population. Using an ecological approach that considers cognitive, social, and environmental factors, correlates of moderate-to-vigorous physical activity (MVPA) and exercise motivation in underserved African American men were examined. Greater exercise motivation, greater social support for exercise, and more favorable environmental perceptions were hypothesized to be associated with higher MVPA, and greater social support and environmental perceptions were hypothesized to be associated with higher exercise motivation. This secondary analysis used baseline data from the Positive Action for Today’s Health (PATH) trial. African American men (n = 166, aged 48 ± 15 years) completed surveys that assessed cognitive, social, and environmental factors theoretically relevant to MVPA. Accelerometers were used to obtain a 7-day estimate of MVPA. Hierarchical linear regression analyses showed that exercise motivation was positively associated with MVPA (B = 1.15, SE = .41, p = .006). Exercise attitudes (B = .16, SE = .07, p = .037), exercise self-concept (B = .28, SE = .06, p < .001), exercise support from friends (B = .12, SE = .06, p = .048), and places for walking and cycling (B = .13, SE = .06, p = .032) were positively associated with exercise motivation. Interventions that improve exercise motivation and associated variables may be warranted to increase MVPA in underserved African American men. ClinicalTrials.gov # NCT01025726